AB0031 Lack of association between CXCL12 RS501120 polymorphism and cardiovascular disease in spanish patients with rheumatoid arthritis. (23rd January 2014) - Lόpez-Mejías, R.; García-Bermúdez, M.; González-Juanatey, C.; Castañeda, S.; Miranda Filloy, J.A.; Gόmez-Vaquero, C.; Fernández, B.; Balsa, A.; Pascual, D.; Blanco, R.; González-Alvaro, I.; Llorca, J.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune inflammatory disease associated with accelerated atherosclerosis [1]. Both a chronic inflammatory response [2]and genetic factors have been implicated in the augmented cardiovascular (CV) mortality observed in these patients. CXCL12 is a chemotactic signal for lymphocytes encoded by the gene CXCL12 . The variant polymorphism rs501120 (T>C), located near of CXCL12 gene, has been associated with CAD [3]. Objectives: We aimed to determine the potential role of CXCL12 rs501120 polymorphism in the risk of CV disease in a large cohort of RA patients. Methods: 1321 Spanish patients with RA were assessed. A subgroup of patients without CV events was also studied to determine the presence of subclinical atherosclerosis by ultrasonography (brachial flow-mediated endothelium-dependent vasodilatation and carotid intima-media wall thickness) Results: No significant differences in genotypic and allelic frequencies between RA patients with and without CV events were observed. It was also the case when values of surrogate markers of atherosclerosis were assessed according to CXCL12 rs501120 genotype frequencies. Conclusions: In conclusion, our results do not confirm an association of CXCL12 rs501120 polymorphism with atherosclerosis neither CV disease in RA. This study was supported by two grants from "Fondo de Investigaciones Sanitarias" PI06-0024 and PI09/007/48 (Spain) and it was partially supported by RETICS Program, RD08/0075 (RIER) from "Instituto de Salud Carlos III" (ISCIII). References: Gonzalez-Gay MA, Gonzalez-Juanatey C, Martin J. Rheumatoid arthritis: a disease associated with accelerated atherogenesis. Semin Arthritis Rheum 2005;35:8-17 Gonzalez-Gay MA, Gonzalez-Juanatey C, Lopez-Diaz MJ, Pineiro A, Garcia-Porrua C, Miranda-Filloy JA et al. HLA-DRB1 and persistent chronic inflammation contribute to cardiovascular events and cardiovascular mortality in patients with rheumatoid arthritis. Arthritis Rheum 2007;57:125-32 Genome-wide association study of 14, 000 cases of seven common diseases and 3, 000 shared controls. Nature 2007;447:661-78 Disclosure of Interest: None Declared